A importância da pesquisa de fontes para os estudos históricos - Mendes, Claudinei Magno Magre [UNESP] (Universidade Estadual de Maringa, 2011)
The importance of research sources for historical studies. In our text we try to call the attention to the fact that, concerning the sources, the most important aspect is the researcher who considers them. This consideration is a product of history, thus in each period and according to his social and political status, the researcher will conceive the sources in a particular way. Therefore, there is no single way to deal with the sources, which is unrelated to how the researcher behaves in relation to contemporary issues.

Em nosso texto procuramos chamar a atenção para o fato de que, na questão das fontes, o aspecto mais importante é o pesquisador que as considera. Essa consideração é produto da história, o que faz com que, em cada época e segundo a posição social e política do investigador, se conceba as fontes de modo particular. Assim, não existe um modo de tratá-las que esteja desvinculada da maneira como o pesquisador se coloca diante das questões do presente.
Keywords: Conception of history; Historiography; Concepção de história; Historiografia